Answer:
Explanation:
Let each side of triangle XYZ have length s. We therefore have:
s = YZ = YQ + QR + RZ = x + 2y
Since each side of triangle X1 Y2 Z2 is 3/4 the length of the corresponding side of triangle XYZ, we have:
3/4s = X1 Z1 = X1 Q + QP + P Z1 = 2x +y.
The system of equations:
x + 2y = s
2x + y = 3/4s
Multiply the second equation by 2, then subtract the first equation.
3x = 1/2s, so x = 1/6s.
Now we have y = 3/4s-2x = 5/12s.
A/[XYZ] = [XYZ] - 3[YPQ]/[XYZ]
= {[XYZ] - 3[(25)/144] * [XYZ]} / [XYZ]
={23/48* [XYZ]} / [XYZ]
= 23/48